INDONESIA AND THE TRANS-PACIFIC PARTNERSHIP AGREEMENT (TPPA): THE LUXURY OF TIME - Price, David (UI Scholars Hub, 2017)
This Presentation examines Indonesia’s recent declaration to join the Trans-Pacific Partnership (TPPA), as announced by President Widodo during a State visit to the United States in October 2015, and his subsequent announcement that this accession would occur within two years. The Presentation explores both the implications for Indonesia of TPPA membership as well as the likelihood of achieving the President’s two-year aspiration. It focuses on one of the more controversial elements of the TPPA, namely, the inclusion of Investor-state dispute settlement (ISDS) provisions, particularly in light of former President Yudhoyono’s 2014 determination to terminate all its bilateral investment treaties with ISDS provisions. In joining the TPPA, Indonesia commits to its ISDS provisions, likely without carve-outs or reservations. The change may perhaps be driven by a perceived imperative to open up Indonesian economy to greater international investment, and to compete with other growing ASEAN economies. However, the future of the TPPA is not necessarily assured, with the U.S. Presidential election and U.S. domestic politics having a major impact on its future status, or even very existence. President Obama considers it a key element of his Presidential legacy, and has Congressional agreement for a “fast-track” vote, but both Presidential candidates, as well as members of both parties in Congress, have at times soundly criticised or even rejected the TPPA. It appears increasingly unlikely that he will succeed in achieving ratification as he enters his Presidency’s “lame duck” period. The Presentation also examines the implications for Indonesia and for the TPPA if the United States unduly delays or even rejects its own domestic ratification of the TPPA.